Karakteristik Fisik dan Kimia Tepung Cangkang Kijing Lokal (Pilsbryoconcha exilis) - Asadatun Abdullah; Nurjanah nurjanah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Local mussel (Pilsbryoconcha exilis) is one aquatic commodity that has high enough potential. Mussel shell is solid waste that has not been used optimally. The purpose of this research is to study the physical and chemical characteristics shells and mussel shell flour with the different of size and body length. The observed parameters include the physical characteristics of shells, yield, chitin, flour yield, degree of white, proximate contents, pH, minerals and mineral solubility determination of mussel shell flour. Mussel obtained from waters Situ Gede has length between 72-103 mm, 31-47 mm high and 13-34 mm thick. Mussel shells in all size contained chitin ranging from 0,72% to 0,75%. Mussel shell flour measuring < 90 mm 20% larger than the size of mussel ≥ 90 mm. Mussel shell flour measuring < 90 mm has a value of 5% degrees whiter than white shell size ≥ 90 mm. Shell flour has a water content between 1,19-1,2%, 93,14-93,34% of ash, 1,85-2,31% of protein, 0,66-0,72% of fat, carbohydrate by difference 2,62-2,94% with a pH range of 8,5-8,9. Mussel shell flour has a mineral content, respectively from the largest which are calcium, phosphorus and magnesium. The calcium and phosphorus mussels flour shell has an optimal value for solubility at pH 2. Mussel shells contained chitin ranged from 0,72% to 0,75%. Mussel shell size difference gave a significantly different effect on the physical characteristics of the mussel shell flour produced but did not influence significantly different to the chemical characteristics of the mussel shell flour produced.